Self-Organized Nanostructured Ag/P2O5/SiO2 Material as a Catalyst for High-Temperature Selective Oxidation of Alcohols; Key Engineering Materials; Vol. 670 : Multifunctional Chemical Materials and Technologies - Knyazev A. S. Aleksey Sergeevich; Magaev O. V. Oleg Valerjevich; Kreyker A. A. Aleksey Aleksandrovich; Mamontov G. V. Grigory Vladimirovich; Dakhnavi E. M. Eldar Musaevich; Knyazeva E. M. Elena Mikhailovna; Vodyankina О. V. Olga Vladimirovna (Chemical Materials and Technologies in Chemical Manufacturing, 2015)
Title screen